Jean-Joseph Rabearivelo au Mercure de France ou les ambiguïtés d'une posture littéraire - Brigitte Rasoloniaina; Claire Riffard (Continents manuscrits)
The "Lettres malgaches" published in the Mercure de France are certainly not as extensive as for other geographical areas: only one issue, in June 1924, with eight pages. It was written by a young Malagasy author, Jean-Joseph Rabearivelo, barely twenty-one years old, and was intended to provide an overview of contemporary Malagasy literature. However, this isolated article fully justifies a study, because it reveals to the literary world of the time - and to today's public - the pen of one of the greatest Malagasy writers, a precursor poet between two worlds; beyond that, because it illustrates the ambiguities of a colonial France advocating assimilation while preventing the full recognition of indigenous talent. The art of the young Rabearivelo – and the interest of this text – lies in highlighting this paradox. Pretending to follow the academic codes of a metropolitan literary review, he bypasses and subverts them by using the oratorical art of the Malagasy kabary (speech), which structures the text.